TANTANGAN PRATEK AKUNTANSI DI RANAH SOSIAL POLITIK - Henry Windrianto Darmoko (Universitas Merdeka Madiun, 2024)
This Study is a narrative research that falls within thw realm of qualitative research. It reveals evidence of the existence of accounting practices in the socio-political sphere, particulary in the context of elections. In Indonesia, political parties participating in elections are required to prepare and submit campaign finance reports to the General Election Commission (KPU). These campaign finance reports are designed based on accounting principles. The reports prepared by political parties are subject to audit by a Public Accounting Firm (KAP) appointed by the KPU. However, the presence of accounting in this socio-political domain faces challenges, as the audit result of the campaign finance reports do not appear to have any impact on the election outcomes or on the participating political parties. Consequently, the auditing of campaign finance reports is deemed a futile exercise, as there is no discernible difference in the election result with or without the audist. Penelitian ini merupakan penelitian naratif yang masuk dalam penelitian kualitatif. Penelitian ini mengungkapkan bukti-bukti eksistensi dari penerapan ilmu akuntansi di ranah sosial politik, khususnya dalam kontek pemilu. Dalam pemilu di Indonesia, partai politik peserta pemilu wajib Menyusun dan menyerahkan laporan dana kampanye kepada KPU. Laporan dana kampanye tersebut didesain dengan konsep akuntansi. Laporan dana kampanye yang telah dibuat oleh partai politik akan diaudit oleh Kantor Akutan Publik (KAP) yang ditunjuk oleh KPU. Dalam eksistensi ilmu akuntansi pada ranah sosial politik ini ternyata memiliki tantangan. Dimana hasil audit atas laporan dana kampanye ternyata tidak memiliki dampak apapun terhadap hasil pemilu ataupun terhadap partai politik peserta pemilu. Sehingga audit atas laporan dana kampanye dikatakan sebagai pekerjaan yang sia-sia karena ada dan tidak adanya audit atas laporan dana kampanye tidak memiliki perbedaan.